Pengaruh Pemahaman Akuntansi dan Pemanfaatan Teknologi Informasi Terhadap Determinasi Kualitas Laporan Keuangan Usaha Mikro Kecil dan Menengah - Sri Ayem; Asih Kentari (Yayasan Literasi Ilmiah Indonesia, 2025)
Purpose: This research aims to examine how accounting literacy and the application of information technology contribute to shaping the quality of financial reports among MSMEs in Gunungkidul. The quality of financial reports is determined by how well they adhere to accounting regulations and provide users with timely, accurate, understandable, and relevant information for making decisions. Method: The research applies a quantitative approach through panel data analysis. For statistical processing, the study relies on EViews 12 SV software. The focus population comprises medium- to lower-tier MSMEs operating in Gunungkidul. Data collection was carried out via questionnaires, resulting in a valid sample of 135 MSME respondents from the region. Finding: The results of this study provide evidence that accounting understanding (X1) and the use of information technology (X2) influence the determinants of the quality of MSME financial reports (Y). Novelty: Variations in research findings lead to inconsistent research and small-scale studies, which have little impact on the caliber of financial reports produced by MSMEs in Gunungkidul. As a result, scholars see a chance to investigate the variables that affect the caliber of financial reports produced by MSMEs in Gunungkidul.